The Origins of Music - Wallin, Nils L.; Merker, Björn; Brown, Steven (London MIT Press, 1999)
What biological and cognitive forces have shaped humankind's musical behavior and the rich global repertoire of musical structures? What is music for, and why does every human culture have it? What are the universal features of music and musical behavior across cultures? In this groundbreaking book, musicologists, biologists, anthropologists, archaeologists, psychologists, neuroscientists, ethologists, and linguists come together for the first time to examine these and related issues. The book can be viewed as representing the birth of evolutionary biomusicology?the study of which will contribute greatly to our understanding of the evolutionary precursors of human music, the evolution of the hominid vocal tract, localization of brain function, the structure of acoustic-communication signals, symbolic gesture, emotional manipulation through sound, self-expression, creativity, the human affinity for the spiritual, and the human attachment to music itself.
Keywords: Music philosophy and esthetics